Standardization of nucleic acid amplification tests in diagnostic molecular microbiology - Alberta Azzi; Federico Chiodo; Marina Crovatto; Valeria Ghisetti; Carlo Mancini; Paolo Ravanini; Marisa Zerbini (Microbiologia Medica, 2008)
Nucleic acid detection by amplification (NAT) assays began to be used in diagnostic microbiology about twenty years ago. Since then, the progress of molecular methods has been continuous and rapid, aimed to obtain more and more sensitive and specific results and automation.To actually achieve such objectives, microbiology laboratories have to use suited quality controls and to participate to external quality control programs. Quality controls for NAT assays need to be adjusted to follow the evolution of the molecular methods.The need of standardization and suited controls for NAT assays became evident approximately by the middle of ’90 years.Thus International Standards (IS) were established by the World Health Organization, for the main blood borne viruses. Such preparations had a well known concentration expressed as International Units, a new measure unit for nucleic acid quantitation. Then, IS were used in order to calibrate working reagents and synthetic calibrators. Another tool for standardization are multicentre studies aimed to verify the performances of participating laboratories using different molecular methods, and allow the comparison of inter-laboratory results.The CoSBio of AMCLI, as other European organizations, in the last years promoted, some multicentre studies on NAT assays. The results of such studies demonstrated a good level of diagnostic performances of participating laboratories. However, with the introduction of the real time PCR (RQ-PCR) a new problem emerged: the variability of results obtained by molecular methods due to different coefficient of linear amplification. Solutions suggested by Literature to this and similar problems are examined, mainly focusing on the assessment of the Calibration curves in the RQ-PCR. Finally, the Authors signal some important fields in the molecular diagnostics, such as the detection of HPV and the detection of BKV, still lacking of sufficient standardization.